Extended Theory Of Planned Behaviour: Investigating Halal Food Purchasing Decisions On Tokopedia E-Commerce In Indonesia - Abdullah Alatas; Abdul Wahab (JURNAL ECONOMINA, 2026)
This study aims to understand the influence of halal food purchase decisions on Tokopedia e-commerce. The model applied involves five independent variables, three variables adopted from the Theory Of Planned Behaviour (TPB) namely attitude, subjective norms and perceived behavioural control and two additional variables namely, halal awareness and lifestyle, as well as one variable that acts as a moderating variable namely religiosity. Furthermore, the dependent variable is only one, namely, the purchase decision. This research was conducted using a quantitative approach with variant-based Structural Equation Model (SEM-PLS) analysis techniques. The data source used is primary data with a sample size of 250 respondents throughout Indonesia, the data was obtained by distributing questionnaires. The test results showed that all variables were significant with a positive direction at 5% alpha. On the other hand, testing the first moderation model, namely the halal awareness variable on purchasing decisions, shows insignificant results or does not contribute because the P-value is greater than the critical value (0.312> 0.05). The second moderation test, namely, the lifestyle variable on purchasing decisions which shows significant results in a negative direction or contributes to weakening with a P-value smaller than the critical value (0.039 <0.05) and a regression coefficient value of -0.094.